2021
DOI: 10.3390/land10080835
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Reclamation and Degradation of Suaeda salsa Saltmarsh along Coastal China’s Northern Yellow Sea

Abstract: Suaeda salsa saltmarshes are an important coastal wetland habitat of China’s northern Yellow Sea, which plays a critical role in sequestering carbon (blue carbon), protecting shorelines, maintaining biodiversity, and has substantial economic value (e.g., ecotourism). However, the area of S. salsa has been rapidly declining due to several different threats from reclamation and invasive species that impact its natural succession. Here, we map the changes in the distribution of the S. salsa saltmarshes along the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Uneven sampling between the two areas was caused by the cessation of research licenses being issued for the nature reserve in 2020 due to the COVID‐19 pandemic, and no permissions were granted to access the private land of the non‐PA during 2018 and 2019. The breeding sites in the PA are located on the west side of the Liaohe river, mainly composed of bare land habitat with sparse S. salsa vegetation restored from formerly used/abandoned local fishery shellfish ponds since 2016 and 2017 (Zhang et al, 2021). Following the abandonment of the small‐scale shellfish ponds, these sites were restored primarily to recreate breeding areas for the endangered and globally threatened Saunders Gull, but have since also been colonized by several other breeding shorebird species including Kentish plover and Pied avocet ( Recurvirostra avosetta ).…”
Section: Methodsmentioning
confidence: 99%
“…Uneven sampling between the two areas was caused by the cessation of research licenses being issued for the nature reserve in 2020 due to the COVID‐19 pandemic, and no permissions were granted to access the private land of the non‐PA during 2018 and 2019. The breeding sites in the PA are located on the west side of the Liaohe river, mainly composed of bare land habitat with sparse S. salsa vegetation restored from formerly used/abandoned local fishery shellfish ponds since 2016 and 2017 (Zhang et al, 2021). Following the abandonment of the small‐scale shellfish ponds, these sites were restored primarily to recreate breeding areas for the endangered and globally threatened Saunders Gull, but have since also been colonized by several other breeding shorebird species including Kentish plover and Pied avocet ( Recurvirostra avosetta ).…”
Section: Methodsmentioning
confidence: 99%
“…showed that human land reclamation was the main reason for the loss and fragmentation of Suaeda salsa saltmarshes from 1988 to 2018. [ 6 ] The rapid degrade of large areas of coastal marine ecosystems worldwide and the lack of effective techniques for reversing this trend have triggered growing interest in recent years. [ 7–10 ]…”
Section: Introductionmentioning
confidence: 99%
“…[5] Recently, Zhang et al showed that human land reclamation was the main reason for the loss and fragmentation of Suaeda salsa saltmarshes from 1988 to 2018. [6] The rapid degrade of large areas of coastal marine ecosystems worldwide and the lack of effective techniques for reversing this trend have triggered growing interest in recent years. [7][8][9][10] In response to widespread declines, a growing number of coastal restoration projects have been conducted in the past decades all around the world, including marsh and mangrove restoration, phytoremediation of coastal saline soil, oyster reefs restoration, seagrass and kelp restoration, living shorelines construction.…”
mentioning
confidence: 99%
“…However, from 1988 to 2009, the entire wetland has been in a state of degradation due to natural and human factors (e.g., aquaculture ponds and drought), especially the ‘red beach’ landscape consisting of the S. salsa community, which not only constrains the development of the local tourism industry but also threatens the wetland’s ecological health [ 6 , 7 ]. Degradation also exists in other coastal wetlands in China, such as the Yellow Sea [ 8 ]. In recent years, the shrinking of the “red beach” has received widespread attention from the government, and, in 2015, a wetland ecological restoration project was launched to restore the beach to its original state.…”
Section: Introductionmentioning
confidence: 99%